Employee Recruitment Decision Support System Using Analytical Hierarchy Process Method in Security Services Companies - Butar Butar, Ribka Sari; Sigalingging, Lasrida; Pramono, Setya; Nuryanto, Uli Wildan; Anderson Butarbutar, Dicky Jhon (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to determine how to combine the AHP method with other techniques to develop an employee recruiting decision support system. Utilized techniques for gathering data include literature reviews, interviews, and observation. The Rapid Application Development system development technique was employed in this study. Unified Model Language is one of the techniques used in system design to help envision the structure of the system that will be created. The discussion's outcomes allow for the following deductions to be made: Using a combination of web-based AHP and SAW methodologies, the Rapid Application Development method, and the Laravel 8 framework, this research creates an employee recruiting decision support system. It is anticipated that the decision support system for staff recruiting will automate the hiring process, reducing applicant subjectivity. HRD's tasks can be made easier by decision support systems, particularly in the data verification process because the electronic files that are received ensure that they are not mixed up with other documents.